GLOBALIZATION AND TOURISM. CASE STUDY - ROMANIA - Daniela Marilena DOROBANȚU; Alina MĂRCUȚĂ; Liviu MĂRCUȚĂ (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
In Romania, the afforestation projects of degraded terrains are carried out in accordance with the technical norms issued by the ministry responsible for forest management. According to recent statistics, across the country there is a significant area of different types of degraded lands, more than 0.4 million hectares being affected by wind erosion. The goal of this study was to highlight the best afforestation alternative for the sandy soils across Oltenia and Carei Plains, corresponding to ecological group number 93 of the Technical Norms regarding the compositions, schemes and technologies for forest regeneration and afforestation of degraded lands. The best alternative resulted by using an Analytic Hierarchy Process, that took into account eight criteria. The combination between black locust and bird cherry proved to be the best choice. The significant area of sandy soils across Romania, but especially the lands from Oltenia and Carei Plains should be regarded rather as an opportunity to increase the forest fund through afforestation than a problem for the local communities and national economy.